Irish norms for the SCORE‐15 and 28 from a national telephone survey. Issue 1 (28th November 2011) - Fay, Declan; Carr, Alan; O'Reilly, Ken; Cahill, Paul; Dooley, Barbara; Guerin, Suzanne; Stratton, Peter
<x xml:space="preserve">Abstract</x> In this study a 29‐item version of the systemic clinical outcome and routine evaluation (SCORE), which contained all items from the SCORE‐15 and SCORE‐28, was used to develop norms for both the 15 and the 28 versions of the SCORE from the same sample. In a random digit dialling telephone survey, a stratified national random sample of 403 adults living in the Republic of Ireland and Northern Ireland completed the SCORE and brief measures of family and personal adjustment. Using receiver operating characteristic curve analyses, cut‐off points for the SCORE‐28 and 15 were found to identify families of children with significant emotional and behavioural problems. We also established 90th percentile points and percentages of cases falling above each scale point for both versions of the SCORE. Confirmatory factor analyses showed that, for both versions of the SCORE, the data fit the three factor solutions found in previous studies. The SCORE scales also had significant correlations with measures of family, parental and child adjustment, and negligible correlations with socioeconomic variables and social desirability response set.